2019
DOI: 10.1007/s11262-019-01691-x
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear localization signal in TRIM22 is essential for inhibition of type 2 porcine reproductive and respiratory syndrome virus replication in MARC-145 cells

Abstract: Porcine reproductive and respiratory syndrome virus (PRRSV) infection causes one of the most economically important swine diseases worldwide. Tripartite motif-containing 22 (TRIM22), a TRIM family protein, has been identified as a crucial restriction factor that inhibits a group of human viruses. Currently, the role of cellular TRIM22 in PRRSV infection remains unclear. In the present study, we analyzed the effect of TRIM22 on PRRSV replication in vitro and explored the underlying mechanism. Ectopic expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 76 publications
0
14
0
Order By: Relevance
“…TRIM25 also inhibits PRRSV replication whereas the N protein antagonizes the antiviral activity by interfering with TRIM25-mediated RIG-I ubiquitination (Zhao et al, 2019). TRIM22 can also reduce PRRSV replication through interacting with N protein nuclear localization signal (Jing et al, 2019b).…”
Section: Other Cellular Pathways Involved In Prrsv Proliferationmentioning
confidence: 99%
“…TRIM25 also inhibits PRRSV replication whereas the N protein antagonizes the antiviral activity by interfering with TRIM25-mediated RIG-I ubiquitination (Zhao et al, 2019). TRIM22 can also reduce PRRSV replication through interacting with N protein nuclear localization signal (Jing et al, 2019b).…”
Section: Other Cellular Pathways Involved In Prrsv Proliferationmentioning
confidence: 99%
“…Study has indicated that the PRRSV-2 N protein can antagonize the antiviral activity of TRIM25 and suppress innate immune responses of the host by competitively interacting with TRIM25, thereby interfering with TRIM25-mediated retinoic acid-inducible gene I (RIG-I) ubiquitination and inhibiting IFN-β production [ 38 ]. TRIM22 can interact with the PRRSV-2 N protein and reduce virus replication, and the SPla and the RYanodine Receptor (SPRY) domain and nuclear localization signal of TRIM22 are indispensable for this interaction [ 39 ]. Moreover, the N-terminal RING domain of TRIM59, which is an important antiviral component, can interact with the C-terminal NendoU domain of nsp11, thereby inhibiting PRRSV-2 infection [ 40 ].…”
Section: The Prrsv–host Interactionsmentioning
confidence: 99%
“…With the rapid development of CRISPR/Cas-based gene editing technology, the acquisition of gene-edited pigs is no longer a difficult task. In this context, the TRIM22 gene has been lost during evolution, and restoring TRIM22 through gene editing will be a potential antiviral strategy [ 39 ]. Furthermore, gene-editing of CD163, which has been determined to be the major receptor, generates pigs resisting PRRSV infection [ 61 ].…”
Section: Current Antiviral Strategies and Prospectsmentioning
confidence: 99%
“…At present, there are few studies on porcine TRIMs participating in virus infection and regulating the immune response. For example, it was reported that the nuclear localization signal of porcine TRIM22 plays a key role in inhibiting type 2 porcine reproductive and respiratory syndrome virus (PRRSV) replication [22], and porcine TRIM21 RING-finger E3 ubiquitin ligase is critical for anti-PRRSV activity [15]. TRIM21 inhibits porcine epidemic diarrhea virus replication by proteasomal degradation of the viral nucleocapsid protein [23], while TRIM21 suppresses foot-and-mouth disease virus (FMDV) infection via specific antibodymediated intracellular neutralization [24].…”
Section: Introductionmentioning
confidence: 99%